Impact of Underweight on the Unsuccessful Treatment Outcome among Adults with Drug-Resistant Tuberculosis: A Systematic Review - Kemas Rakhmat Notariza; Jaka Pradipta (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2022)
Background: The emergence of drug-resistant (DR) strains of Mycobacterium tuberculosis has disrupted the control of tuberculosis (TB) problem worldwide. Most of DR-TB patients presents with underweight problems. Prior studies showed that body mass index affects sputum conversion and could be a predictor of treatment outcome, but the causal relationship has not been established yet. This systematic review aimed to determine the impact of underweight on the unsuccessful treatment outcome among adults with DR-TB.Methods: Systematic literature search and handsearching were done in four databases: Cochrane, Proquest, Pubmed, and ScienceDirect. Filtering process by using selection criteria yielded 4 eligible articles (2 prospective cohort and 2 retrospective cohort studies) for answering the clinical question. Critical appraisal was conducted by using the Newcastle-Ottawa Quality Assessment Scale (NOS).Results: All four studies were assessed as having high quality according to the NOS score. The findings of all eligible studies were consistent in revealing the impact of underweight on the unsuccessful treatment outcome in DR-TB, with the relative risk: 2.194 (95% confidence interval [CI], 1.134–4.246), 1.771 (95% CI, 1.069–2.931), 3.465 (95% CI, 1.114–2.712), and 4.703 (95% CI, 1.709–12.947), consecutively. The number needed to harm (NNH) of 3–7 indicated the clinically meaningful harm of the exposure. This systematic review showed that one poor outcome incidence could be found with only a few underweight DR-TB patients.Conclusion: Underweight increased the risk of unsuccessful treatment outcome among adults with DR-TB. Low baseline body weight (<40 kg) could be another considerable factor in anticipating the poor treatment outcome.